Determining the factors affecting the acceptance of social commerce in service-oriented businesses using the fuzzy Delphi method. (8th February 2022) - Pouti, Nasibeh; Taghavifard, Mohammad Taghi; Taghva, Mohammad Reza; Fathian, Mohammad
Social commerce has emerged as a new paradigm in business and commerce for nearly a decade. The first attempt to apply this paradigm is to identify the factors affecting its acceptance studied in several research works. To achieve the purpose of the study, we conducted a systematic review of research related to the adoption and use of social media in business in the period 2010 to 2019. Based on the three stages of searching, screening and retrieving, and completing the databases, we identified 224 related studies. The confirmed factor relations in the studies were identified. By integrating synonymous factors, 228 factors were identified as influencing factors on social commerce acceptance from the users' point of view. Then, we attempted to identify the most important influential factors based on three screening stages. Finally, the experts examined the remaining factors using the fuzzy Delphi method.